Stark-Zeeman Broadening of Spectral Line Shapes in Magnetized Plasmas - Kamel Ahmed Touati; Keltoum Chenini; Mohammed Tayeb Meftah (Atoms, 2020)
In this work, we studied the Lyman-alpha line in the presence of a magnetic field, such as the ones found at the edge of tokamaks. The emphasis is on the contribution of the motional Stark effect on line broadening, which may have comparable effects to the internal plasma microfields for the spectral line in question. The effect of the magnetic field, temperature, and the Maxwell distribution of the ion velocities and density on Lyman-alpha are studied.